The Expression is
(x^-2y^-4x³)^-2
We can combine the x terms inside the brackets using the concept;
x ^a × x^b = x^(a+b)
Therefore,
(x^-2)(x^3) = x^(3-2) = x^!
Thus we get;
(xy^-4)^-2
Using the concept
(x^a)^b = x^(ab)
Therefore
= x ^(-2×1) y^(-2×-4)
=x^-2y^8
But using the concept; x^-a = 1/x^a
Thus, x^-2y^8 = y^8/x²
Hence the simplified equation is;
= y^8/x²
Answer:
Step-by-step explanation:
3x + 18 = 30
3x + 18 -18 = 30 - 18
3x = 12
x = 4
Hello, what’s the question though
Answer:
Step-by-step explanation:
12x³ = 2²·3·x³
The greatest common factor of 12x³ and 3x² is 3x².
12x³ - 3x² = (4x - 1)3x²
The answer will be 3/5
to find the slope you must use the formula
y1-y2/x1-x2.